Production of Induced Secondary Metabolites by a Co-Culture of Sponge-Associated Actinomycetes, Actinokineospora sp. EG49 and Nocardiopsis sp. RV163 - Yousef Dashti; Tanja Grkovic; Usama Ramadan Abdelmohsen; Ute Hentschel; Ronald J. Quinn (Marine Drugs, 2014)
Two sponge-derived actinomycetes, Actinokineospora sp. EG49 and Nocardiopsis sp. RV163, were grown in co-culture and the presence of induced metabolites monitored by 1H NMR. Ten known compounds, including angucycline, diketopiperazine and β-carboline derivatives 1–10, were isolated from the EtOAc extracts of Actinokineospora sp. EG49 and Nocardiopsis sp. RV163. Co-cultivation of Actinokineospora sp. EG49 and Nocardiopsis sp. RV163 induced the biosynthesis of three natural products that were not detected in the single culture of either microorganism, namely N-(2-hydroxyphenyl)-acetamide (11), 1,6-dihydroxyphenazine (12) and 5a,6,11a,12-tetrahydro-5a,11a-dimethyl[1,4]benzoxazino[3,2-b][1,4]benzoxazine (13a). When tested for biological activity against a range of bacteria and parasites, only the phenazine 12 was active against Bacillus sp. P25, Trypanosoma brucei and interestingly, against Actinokineospora sp. EG49. These findings highlight the co-cultivation approach as an effective strategy to access the bioactive secondary metabolites hidden in the genomes of marine actinomycetes.